Effect of exergame-based balance training on selective attention and inhibitory control measured via eye tracking among healthy young adults - Saud, Unaisa (2021)
Introduction: “Exergames” or active video games have emerged as promising tools that provide additive benefits of both physical exercise and gaming in an interactive technology-based approach. Previous studies demonstrated exergaming induced cognitive improvements, however, exergames focusing on balance mostly studied its effect on reducing falls and improving posture. Hence, there exists a need to assess whether exergame-based balance training can generate cognitive enhancement. Objective: To determine whether an intervention using an exergaming equipment called “Fitness Balance Board” (FIBOD) can improve the cognitive functions of selective attention and inhibitory control among healthy young adults (18-35 years). Methodology: A randomised control trial design with stratified randomisation was implemented. Thirty healthy undergraduate students (Mean Age: 22.3, SD = 1.4) from Universiti Sains Malaysia were recruited and completed the study, with fifteen participants assigned to a 4-weeks exergaming group, and fifteen participants assigned to a passive control group. The study implemented eye-tracking in a “Visual Search Task” (VST) and “Antisaccade Task” (AST) paradigm as measures of selective attention and inhibitory control respectively. Results: Separate 2x2 mixed ANOVAs tested four hypotheses of this study. As hypothesised, compared to pre-test, at post-test, exergamers were significantly more accurate (Adjusted Mean Difference = 2.8%, p = .008), made less number of fixations (Adjusted Mean Difference = .45 , p < .001), and had faster time to first fixation (TTFF) on target (Adjusted Mean difference = 132.5ms, p < .001) in VST. Exergamers also made less fixations and had faster TTFF at search with most number of items (20 items) at post-test (Mean number of fixations: 4.6, SD = 1.04; TTFF: 689.8ms , SD = 136.9) compared to search with lesser number of items (15 items) (Mean number of fixations: 4.7, SD = 1.29; TTFF :738.6ms, SD = 189.8). In AST, as hypothesised, exergamers had faster antisaccade reaction times at post-test compared to pre-test (Adjusted Mean difference = 51.9ms, p < .001). Contrary to hypothesis, exergamers did not reduce antisaccade errors. In comparison, control group did not significantly improve in any outcome measures from pre to post-test. Conclusion: Exergame-based balance training using FIBOD was feasible to improve selective attention and inhibitory control of healthy young adults. Future research can further explore changes in search patterns related to exergame play to establish an understanding of exergame related cognitive improvements.